Effect of Sleeve Gastrectomy With Pancreatic Omentoplasty On Pancreatic Vegf Intensity In Non-Obesity Diabetes Mellitus Rats - Mughni Abdul; Chemy Wiryawan; Reza Tri Sutrisno; Vito Mahendra; Dimas Erlangga (Green Publisher Indonesia, 2022)
Diabetes mellitus is one of the most common non-communicable diseases that that is still growing today especially diabetes mellitus type 2 (DMT2). Diabetes in non-obese patients is an important problem to solve because it tends to be worse than DM in obese patients. Chronic hyperglycemia can damage body tissues through several mechanisms like polyol pathway, hexosamine pathway, activation of protein kinase C (PKC) and advance glycation end products (AGEs). This pathway can damage the pancreas so that insulin cannot be secreted and worsen the condition of diabetes. Sleeve gastrectomy procedure can secrete hormones such as insulin, GLP-1, PYY (Peptide YY) dan PP (Pancreatic polypeptide) which play a role in the regulation of glucose in the blood. Omentoplasty can play a role in cell regeneration, especially Langerhans β cells so that insulin can be produced adequately. Objective to evaluate the effect of Sleeve Gastrectomy and Pancreas Omentoplasty on Pancreatic VEGF Intensity in non-obese diabetes mellitus rats. Methods True experimental study with